2007
DOI: 10.1016/j.vetmic.2007.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Experimental staphylococcal mastitis in bitches: Clinical, bacteriological, cytological, haematological and pathological features

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.A c c e p t e d M a n u s c r i p t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 21 publications
0
41
0
3
Order By: Relevance
“…Mastitis may infrequently occur from hematogenous spread of organisms, nonlactation-associated trauma, fight wounds, or infected neoplasms. A complete blood count may reveal an inflammatory leukogram characterized by either an increase in segmented and nonsegmented (band) neutrophils or a degenerative left shift with a predominance of immature neutrophils, especially if gangrenous mastitis is present (Ververidis et al, 2007). Mastitis is most often associated with postparturient lactation.…”
Section: Mammary Gland Inflammation/infectionmentioning
confidence: 99%
“…Mastitis may infrequently occur from hematogenous spread of organisms, nonlactation-associated trauma, fight wounds, or infected neoplasms. A complete blood count may reveal an inflammatory leukogram characterized by either an increase in segmented and nonsegmented (band) neutrophils or a degenerative left shift with a predominance of immature neutrophils, especially if gangrenous mastitis is present (Ververidis et al, 2007). Mastitis is most often associated with postparturient lactation.…”
Section: Mammary Gland Inflammation/infectionmentioning
confidence: 99%
“…The smears were stained by using the May-Grünwald Giemsa (MGG), (E. Merk, Darmstadt, Germany) technique, followed by optic microscopic interpretation (Ververidis et al, 2007).…”
Section: Materials and Methodesmentioning
confidence: 99%
“…hyicus (Aráujo et al, 2011) and Staph. intermedius (Ververidis et al, 2007) have been reported to cause acute mammary infections.…”
Section: Introductionmentioning
confidence: 99%
“…Κάποιες από αυτές τις ε στίες χρόνιας μαστίτιδας, που διατηρούνται σε ΰφεση κατά την περίοδο αδράνειας των μαστικών αδένων, μπορούν να οδηγήσουν σε αναζωπύρωση της μόλυν σης, με εκδηλώσεις οξείας μαστίτιδας, σε επόμενη γα λουχία ή σε περιπτώσεις ψευδοκΰησης. Η μόνη πειραματική μελέτη οξείας μαστίτιδας σε σκύλους που περιγράφεται στην παγκόσμια βιβλιο γραφία έχει πραγματοποιηθεί στην Ελλάδα και γι' αυ τό αναλύεται εκτενέστερα (Ververidis et al 2006(Ververidis et al , 2007. Οι ερευνητές προκάλεσαν κλινική μαστίτιδα σε θηλυκούς σκύλους μετά από ενδομαστικό ενοφθαλμι σμό τους με S. intermedins.…”
Section: ή ακόμη και αιματογενώς (Linde-forsberg 2005)unclassified